2022
DOI: 10.20853/36-1-4560
|View full text |Cite
|
Sign up to set email alerts
|

University lecturers’ preparedness to use technology in teacher training of mathematics during COVID-19: The case of Ethiopia

Abstract: The study aimed to investigate Ethiopian university lecturers’ readiness to use technology for teaching mathematics at the tertiary level during the COVID-19 pandemic when they were compelled to adapt to distant education. Using Google Forms, online questionnaires were distributed to 41 lecturers in three Ethiopian universities, of whom eighteen participated. Before the research, the questionnaire was piloted with eight lecturer participants to categorise questions and validate the instrument using the Rasch m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…Personal challenges were also reported in a study by Owusu-Fordjour, Koomson and Hanson (2020) on Ghanaian tertiary students who indicated a lack of preparedness for self-guided learning from home during the COVID-19 pandemic. The current study findings further resonate with Machaba and Bedada (2022), whose study found that institutional and personal factors posed challenges to the use of technology in the higher education environment during the COVID-19 pandemic. However, the study partially diverges from the findings by Machaba and Bedada (2022) in that the prominent barriers to the integration of technology into teaching and learning processes rather proved to be at the institutional level.…”
Section: Discussionsupporting
confidence: 85%
“…Personal challenges were also reported in a study by Owusu-Fordjour, Koomson and Hanson (2020) on Ghanaian tertiary students who indicated a lack of preparedness for self-guided learning from home during the COVID-19 pandemic. The current study findings further resonate with Machaba and Bedada (2022), whose study found that institutional and personal factors posed challenges to the use of technology in the higher education environment during the COVID-19 pandemic. However, the study partially diverges from the findings by Machaba and Bedada (2022) in that the prominent barriers to the integration of technology into teaching and learning processes rather proved to be at the institutional level.…”
Section: Discussionsupporting
confidence: 85%
“…Students felt that it was difficult to practice online learning especially in understanding the content for the subjects related with calculations. This lack of knowledge could be caused by the lack of technology training and technical support (Machaba & Bedada, 2022). Most teachers and students are not physically and mentally ready for online teaching and learning when they lack the knowledge and skills in using digital media.…”
Section: Issues and Challenges Of Online Teaching And Learningmentioning
confidence: 99%
“…However, Telegram, through its affordability and flexibility, is such a social media application that makes the world smaller (Aghajani & Adloo, 2018;Aladsani, 2021;Swartz et al, 2022) as it gives students a chance to communicate and interact with other students across geographical barriers. Although e-Learning technologies and mobile learning (m-learning) awareness are ever-increasing (Aladsani, 2021;Dollah et al, 2021;Sevnarayan, 2022;Sevnarayan & Mohale, 2022), lecturers' competences and skills are "challenged when faced with a new reality where digital teaching becomes the primary, if not the only, mode of instruction" (Machaba & Bedada, 2022). Lecturers are opposed to the use of Telegram and other social media applications, as they are unaware of its benefits (Dollah et al, 2021).…”
Section: Introductionmentioning
confidence: 99%